ANALYSIS OF METHODS AND MEANS OF DETERMINATION OF THE FACTORY OF OIL PIPELINES AND THE CALCULATION OF THEIR RESIDUAL RESOURCES - Martyniuk, R. T.; Chernova, O. T.; Shyan, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The basic principle of diagnosing long-life metal structures, and pipelines in particular, is based on consistent and systematic measurements of certain design parameters, on detecting changes in these parameters during operation and comparing them with the original ones, and on predicting changes in these parameters. The application of technical diagnostics and non-destructive testing methods to determine the actual technical status is a regular technological operation and, as experience shows, an effective way of ensuring the technical reliability and safe operation of pipelines and the gas transmission system as a whole. The methods of non-destructive testing, correlation analysis and modern methods of statistical processing of experimental and reference data (artificial neural networks) were used to determine the actual state of oil and gas pipelines. Factor and regression analysis methods were used during theoretical studies. In the course of the experimental studies, the methods of experiment planning, probability theory were used.